The Predictive Role of Interpersonal Sensitivity and Emotional Self-Efficacy on Psychological Resilience Among Young Adults - AYDOĞDU, BİLGE NURAN; EKŞİ, HALİL; ÇELİK AHBAB, HİLAL (ANI YAYINCILIK, 2017)
Purpose: In the face of adverse and traumatic events throughout their lives, individuals respond in different ways depending on their degree of resilience, factors of which include their individual resources for coping with those events. This study examined the predictive role of emotional self-efficacy and interpersonal sensitivity on psychological resilience among young adults in order to gain insights into psychological resilience and its protective factors. In particular, its purpose was to examine how perceiving emotions of the self and others, using emotions to facilitate thought, regulating emotions in the self and others, interpersonal awareness, need for approval, separation anxiety, timidity, fragile inner self, and understanding emotions, the emotional self, and others affect perceptions of the future, structural style, social competence, family cohesion, and social resources. Method: Using the relational screening model, participants were selected via basic random sampling. The sample included volunteers-243 women (73.4%) and 88 men (26.6%)-with a mean age of 21.46 years. The Resilience Scale for Adults, Emotional Self-Efficacy Scale, and Interpersonal Sensitivity Measure were used as measuring instruments. Findings: Following simultaneous multiple regression analysis, psychological resilience could be predicted according to emotional self-efficacy and interpersonal sensitivity. Conclusions and Recommendations: Similar to earlier research in the field, this study showed that psychological resilience and its aspects can be explained in light of emotional self-efficacy and interpersonal sensitivity. However, since psychological resilience had not heretofore been examined in such detail, this study offers significant contributions to trauma and preventive psychological counselling studies. (C) 2017 Ani Publishing Ltd. All rights reserved.
Keywords: psychological resilience; interpersonal sensitivity; emotional self-efficacy; young adults; SCALE; TEMPERAMENT; DIMENSIONS; CHILDREN; VALIDITY; THERAPY; PARENTS; ANXIETY; RISK